Territorial capital – a specific feature of territory - Łuczyszyn, Tomasz (Kapitał terytorialny specyficzną cechą terytorium, 2024)
Aim: The aim of the article is the theoretical analysis of territorial capital in the context of its essence, the elements that determine it, and the role it plays in development policy. Methodology: The research was based on the qualitative and quantitative approach. The methods applied are primarily the descriptive method and critical analysis of literature on local development, intangible resources and the theory of territoriality. Case studies of selected autonomous territories in Poland (e.g. municipalities with developed bottom-up strategies) are also conducted. Results: An increase in the importance of intangible resources (social trust, relational capital) as a key factor of development was identified. The important role of informal local coalitions in creating development policy, regardless of formal structures, was noted. Implications and recommendations: Local development policy should take into account the unique social and relational structure of a given territory. Mechanisms are needed to support local autonomy in the creation of development strategies – especially bottom-up ones. Recommended reorientation of financing tools (e.g. EU funds) from hard investments to soft and networking activities. Originality/value: The author addresses a current and insufficiently researched area: the role of intangible resources in local politics. He combines the socio-relational approach with the spatial-economic approach, indicating their complementarity. It provides specific tools for diagnosing and strengthening the development potential of local and regional areas.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 151-158
Keywords: territorial capital; territory; location; kapitał terytorialny; terytorium; lokalizacja